2021
DOI: 10.3389/fmed.2021.629671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile, Prognostic Factors, and Outcome Prediction in Hospitalized Patients With Bloodstream Infection: Results From a 10-Year Prospective Multicenter Study

Abstract: Background: Bloodstream infection (BSI) is one of the most common serious bacterial infections worldwide and also a major contributor to in-hospital mortality. Determining the predictors of mortality is crucial for prevention and improving clinical prognosis in patients with nosocomial BSI.Methods: A nationwide prospective cohort study was conducted from 2007 until 2016 in 16 teaching hospitals across China. Microbiological results, clinical information, and patient outcomes were collected to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Bloodstream infections are most common (37/131 studies, 28%) severe infections among reported studies, and Acinetobacter baumannii is the top pathogen (52/131 studies, 38.5% and 4395/11,546 patients, 38%) [ 1 ]. The mortality of Acinetobacter baumannii -related bloodstream infections showed an increasing trend in a 10-year prospective study in China [ 2 ]. There is an urgent need for rational and effective medication schemes to be developed in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Bloodstream infections are most common (37/131 studies, 28%) severe infections among reported studies, and Acinetobacter baumannii is the top pathogen (52/131 studies, 38.5% and 4395/11,546 patients, 38%) [ 1 ]. The mortality of Acinetobacter baumannii -related bloodstream infections showed an increasing trend in a 10-year prospective study in China [ 2 ]. There is an urgent need for rational and effective medication schemes to be developed in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the characteristics of multidrug-resistance or extensively drug-resistance, the infections caused by A. baumannii isolates were usually associated with high mortality, particularly in the bloodstream and central nervous system infections ( 9 ). An increasing trend was observed in the mortality of patients infected with A. baumannii from a 10-year prospective multicenter study in hospitalized patients with bloodstream infection ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide prospective cohort study conducted from 2007 to 2016 in 16 teaching hospitals across China suggested that A. baumannii was one of the top four pathogens responsible for bacteremia, accounting for approximately 7.03% of bloodstream bacterial isolates [21] . Data from the China Antimicrobial Surveillance Network (CHINET) revealed signi cant increases in the rates of resistance to carbapenem antibiotics, which ranged from 31% in 2005 to 79.2% in 2018 [22] .…”
Section: Discussionmentioning
confidence: 99%